2022
DOI: 10.3389/fpsyg.2022.798759
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership, Trust (in the Leader), and Flourishing: Does Precariousness Matter?

Abstract: OrientationThis study employed a second stage moderated mediation analysis to investigate the influence of authentic leadership on employee flourishing via trust in the leader (mediating variable) and job overload (moderating variable).Research PurposeTo explore the relationship between authentic leadership and flourishing by considering the indirect effect of trust in the leader as potentially moderated by job overload.Motivation for the StudyAn authentic leadership style, trust in the leader, and job overloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 126 publications
1
10
0
Order By: Relevance
“…This aligns with previous research, which has established that flourishing is closely connected to emotional, psychological, and social well‐being (Eraslan‐Capan, 2016). Moreover, flourishing is associated with positive relationships, life purposes, personal growth, and authentic leadership styles (Fowers et al., 2016; Kleynhans et al., 2022). Additionally, research has shown that social media use can have a positive impact on flourishing, particularly when individuals have positive experiences and draw inspiration from others on social media (Marciano & Viswanath, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with previous research, which has established that flourishing is closely connected to emotional, psychological, and social well‐being (Eraslan‐Capan, 2016). Moreover, flourishing is associated with positive relationships, life purposes, personal growth, and authentic leadership styles (Fowers et al., 2016; Kleynhans et al., 2022). Additionally, research has shown that social media use can have a positive impact on flourishing, particularly when individuals have positive experiences and draw inspiration from others on social media (Marciano & Viswanath, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Recognising this, researchers have devoted substantial attention to understanding how, by engaging in different leadership styles and behaviours, leaders can (a) foster an environment that supports group members to flourish (e.g. [ 111 , 112 ]) and (b) help protect against (or, conversely, contribute to) work groups becoming toxic (see [ 113 ] for a review). Very few studies with these goals have been conducted in sport (see [ 114 ] for an exception).…”
Section: A Social Identity Approach To Athlete Mental Healthmentioning
confidence: 99%
“…Recent studies found that authentic leadership could be beneficial to organizations, as it was associated with a variety of positive end results, such as follower creativity, team member performance ( Duarte et al, 2021 ), consumer focus, personnel retention ( Ribeiro et al, 2020 ), and employee flourishing ( Nair et al, 2021 ; Kleynhans et al, 2022 ). Ryff and Keyes (1995) maintain that when leaders exhibit behavior linked to the dimensions of authentic leadership (self-awareness, internalized moral perspective, balanced processing, and relational transparency), they can influence the well-being of employees.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…The central research question that can be asked is whether authentic leadership will positively influence employee attitudes in times of uncertainty? We know that authentic leadership is a positive predictor of organizational support ( Aria et al, 2019 ; Baykal, 2020 ), trust in the organization ( Stander et al, 2015 ; Coxen et al, 2016 ), and flourishing ( Chevalier et al, 2021 ; Kleynhans et al, 2022 ). However, it is not clear to what extend the impact on each other play in a model incorporating all the constructs.…”
Section: Introductionmentioning
confidence: 99%